Optimization of cyclodextrin glucanotransferase production from Bacillus clausii E16 in submerged fermentation using response surface methodology - Alves-Prado, Heloiza Ferreira; Bocchini, Daniela Alonso; Gomes, Eleni; Baida, Luis Carlos; Contiero, Jonas [UNESP]; Roberto, Ines Conceicao; Da Silva, Roberto (Humana Press Inc, 2007)
Cyclodextrin glucanotransferase production from Bacillus clausii E16, a new bacteria isolated from Brazilian soil samples was optimized in shake-flask cultures. A 2 4 full-factorial central composite design was performed to optimize the culture conditions, using a response surface methodology the combined effect among the soluble starch concentration, the peptone concentration, the yeast extract concentration, and the initial pH value of the culture medium was investigated. The optimum concentrations of the components, determined by a 2(4) full-factorial central composite design, were 13.4 g/L soluble starch, 4.9 g/L peptone, 5.9 g/L yeast extract, and initial pH 10.1. Under these optimized conditions, the maximum cyclodextrin glucanotransferase activity was 5.9 U/mL after a 48-h fermentation. This yield was 68% higher than that obtained when the microorganism was cultivated in basal culture medium.
Keywords: alkalophillus Bacillus clausii; CGTase production; cyclodextrin glucanotransferase; experimental design; submerged fermentation; response surface methodology